Re-evaluation of a Neonatal Mouse Model of Infection With Enterotoxigenic Escherichia coli - Carroll, Carla J.; Hocking, Dianna M.; Azzopardi, Kristy I.; Praszkier, Judyta; Bennett-Wood, Vicki; Almeida, Kaylani; Ingle, Danielle J.; Baines, Sarah L.; Tauschek, Marija; Robins-Browne, Roy M. (Frontiers in Microbiology, 2021)
Enterotoxigenic E. coli (ETEC) is a common cause of diarrhea in children in low- and middle-income countries, and in travelers to these countries. ETEC is also an important cause of morbidity and premature mortality in piglets, calves, goat kids and lambs. The major virulence determinants of ETEC are enterotoxins and colonization factors, which enable the pathogen to colonize the small intestine and deliver enterotoxins, such as the heat-stable enterotoxins, STp and STh, to epithelial cells. Because most ETEC strains are host-specific, there are few convenient animal models to investigate the pathogenesis of ETEC infections or to evaluate specific anti-ETEC interventions, such as drugs and vaccines. An exception is ETEC strains bearing F41 pili, which mediate intestinal colonization of various young animals, including neonatal mice, to cause disease and in some cases death. In this study, we used the archetypal F41-producing bovine ETEC strain, B41 (O101:NM; K99, F41, STp) to validate and further explore the contribution of F41 and STp to bacterial virulence. By using targeted gene deletion and trans-complementation studies, augmented by whole genome sequencing, and in vitro and animal studies of virulence, we established that F41 mediates colonisation of the mouse intestine and is essential for bacterial virulence. In addition, we showed for the first time that STp is as important as F41 for virulence. Together, these findings validate the use of neonatal mice to study the pathogenesis of F41-bearing ETEC and to investigate possible specific anti-ETEC interventions including vaccines that target the heat-stable enterotoxins.